Role of the private sector in implementing an OECS economic development strategy - Ducreay, Glen (Dominica Association of Industry & Commerce RoseauDM, 1993)
Posits that the traditional private sector must fully incorporate farmers and farmer's organizations as equal partners in the development process. Sees a need for training for farmers and the rest of the private sector. Suggests that there should be increased private sector investment in agriculture in the light of what is happening with OECS bananas. Opines that the linkage between agriculture and tourism in the procurement of food and beverage must be deepened.